Aksesibilitas Bagi Pemustaka Difabel di UPT Perpustakaan Universitas Tadulako - Andriani, Dinar Ayu; Nurdin, Nurdin; Dakhalan, Andi Muhammad (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2023)
This research aims to investigate the availability of library accessibility for disabled library users and the challenges faced by librarians in serving disabled library users at the UPT Library of Tadulako University. The research method used is descriptive qualitative research, with the research location at the UPT Library of Tadulako University. Data were obtained from primary and secondary data sources through data collection techniques such as observation, interviews, and documentation, which were then analyzed through data reduction, data presentation, and data verification. The results of the research show that accessibility for disabled library users at the UPT Library of Tadulako University is already available with adequate access for wheelchair users, accessible entrance doors, tables, and easily reachable shelves. However, the toilets still do not meet the standards set by the IFLA Checklist. In addition, the service provided by librarians to deaf library users is still limited to written communication because there are no librarians who are able to use sign language. Based on the research findings, it is recommended that library management add librarians who have special expertise in serving disabled library users, especially for deaf library users. In addition, it is also necessary to add adequate accessibility facilities and infrastructure for disabled library users, following the development of the campus that is becoming an inclusive campus. It is hoped that the results of this research can contribute to improving the quality of library accessibility for disabled library users at the UPT Library of Tadulako University. Abstrak Penelitian ini bertujuan untuk menginvestigasi ketersediaan aksesibilitas perpustakaan bagi pemustaka difabel dan kendala-kendala yang dihadapi oleh pustakawan dalam melayani pemustaka difabel di UPT Perpustakaan Universitas Tadulako. Jenis penelitian yang digunakan adalah penelitian kualitatif deskriptif, dengan lokasi penelitian di UPT Perpustakaan Universitas Tadulako. Data diperoleh dari sumber data primer dan sekunder melalui teknik pengumpulan data seperti observasi, wawancara, dan dokumentasi, yang kemudian dianalisis melalui reduksi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan bahwa aksesibilitas bagi pemustaka difabel di UPT Perpustakaan Universitas Tadulako sudah tersedia dengan akses jalan yang memadai bagi pengguna kursi roda, pintu masuk, meja, dan rak yang mudah dijangkau. Namun, toilet masih belum memenuhi standar yang ditetapkan oleh IFLA Checklist. Selain itu, pelayanan yang diberikan oleh pustakawan kepada pemustaka tunarungu masih terbatas pada komunikasi tertulis karena tidak ada pustakawan yang mampu menggunakan bahasa isyarat. Berdasarkan kesimpulan penelitian, disarankan agar pengelola perpustakaan menambahkan pustakawan yang memiliki keahlian khusus dalam melayani pemustaka difabel, terutama untuk pemustaka tunarungu. Selain itu, perlu juga menambahkan sarana dan prasarana aksesibilitas yang memadai bagi pemustaka difabel, mengikuti perkembangan kampus yang sedang berkembang menjadi kampus inklusi. Diharapkan hasil penelitian ini dapat memberikan kontribusi dalam meningkatkan kualitas aksesibilitas perpustakaan bagi pemustaka difabel di UPT Perpustakaan Universitas Tadulako.